Investigation on V2O5 Thin Films for Field Effect Transistor Applications - S. K. Suresh Babu; D. Jackuline Moni; D. Gracia; Amsalu Gosu Adigo (Advances in Materials Science and Engineering)
V2O5 thin films are analyzed for the substitution of SiO2 to reduce the leakage current in devices when SiO2 becomes ultrathin in submicron technology. Vanadium pentoxide (V2O5) has a high-k dielectric constant of 25 and can be replaced as a gate oxide in the field-effect transistor. V2O5 is deposited using pulsed laser deposition (PLD) in the oxygen (O2) environment at room temperature and characterized. The films surface morphology has been examined by scanning electron microscopy. The capacitance, dielectric constant, and dielectric loss are analyzed for fabricated metal oxide semiconductor (MOS) structure using Solartron SI-1260 impedance analyzer. The transfer characteristic of the fabricated device is analyzed using National Instruments NI-PXI 4110. The ION/IOFF ratio of 106 and threshold voltage (VTH) of 0.6 V is obtained.